2019
DOI: 10.1101/791764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated analysis of sleep in adultC. eleganswith closed-loop assessment of state-dependent neural activity

Abstract: Sleep, a state of quiescence associated with growth and restorative processes, is conserved across species. Invertebrates including the nematode Caenorhabditis elegans exhibit sleep-like states during development and periods of satiety and stress.Here we describe two methods to study behavior and associated neural activity during sleep and awake states in adult C. elegans. A large microfluidic device facilitates population-wide assessment of long-term sleep behavior over 12 h, including effects of fluid flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
1
0
0
Order By: Relevance
“…Our findings are in line with other studies that have shown the strong antioxidant ability of various Essiac® formulations in combating different forms of ROS [14][15][16]. While we recognize that the results of our work conducted in C. elegans cannot be directly extended to humans, this model's 70% genetic and 87% developmental similarities to humans [32] has justified its extensive use in diverse research endeavors spanning neurological, developmental, and toxicological fields [22,24,25,33,34]. Interestingly, the only reports of any harmful effects related to human consumption of Essiac ® have been mild nausea, bad aftertaste, and diarrhea [10,21].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are in line with other studies that have shown the strong antioxidant ability of various Essiac® formulations in combating different forms of ROS [14][15][16]. While we recognize that the results of our work conducted in C. elegans cannot be directly extended to humans, this model's 70% genetic and 87% developmental similarities to humans [32] has justified its extensive use in diverse research endeavors spanning neurological, developmental, and toxicological fields [22,24,25,33,34]. Interestingly, the only reports of any harmful effects related to human consumption of Essiac ® have been mild nausea, bad aftertaste, and diarrhea [10,21].…”
Section: Discussionsupporting
confidence: 87%